Pilihan-Pilihan Akuntansi dalam Aplikasi Teori Akuntansi Positif - Tatang Ary Gumanti (Jurnal Akuntansi dan Auditing Indonesia, 2002)
Empirical researches based on the positive accounting theory or the economic consequence theory have directed to seek for the answers about the reasons that motivate managers in selecting or determining certain accounting techniques in preference to other techniques. So far the existing studies have found an association between the firms’ specific characteristics and managers’ decision to select certain accounting techniques. That is, there is specific reason of why manager prefers to use one accounting method but not the others. Further study needs to be conducted to seek the answers whether managers have specific reasons or behave opportunistically by adopting accounting techniques that affect the firm accounting performance for which the selected techniques do not against the generally accepted accounting principles (accounting standards). Key words: Accounting techniques (methods), positive accounting theory, opportunistic behavior, accounting regulations.